Saint Vincent and the Grenadines. Significant achievements 2014 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamerica de Cooperación para la Agricultura (IICA), 2016)
The main activities carried out by the Institute in San Vicente and the Grenadines during 2014 are identified, with regard to the needs and interests of the country, strengthening on topics such as sustainability, governance, vulnerability, climate change, good agricultural practices, watersheds, production of vegetables and hogs and in emergency care provoked by storms.